A importância da administração para a agroindustrialização familiar e sua influência no desenvolvimento rural sustentável - Pavinato, Julie Mathilda Semiguem (2018)
This research depicts aspects of the management of agro-industries and the administrative praxis of institutions that are related to Ubiratã-PR municipality in order to find out how Administration science may contribute to agribusiness family improvement and thus influence the sustainable rural development. Thus, this research aimed at analyzing if the management and administrative practices, employed by institutions related to agro-industrialization in this city as well as their own agribusinesses, have provided better conditions of work and life to improve farmers’ families. This research is characterized as exploratory and descriptive about typology, dialectic and phenomenological, concerning the method, and qualityquantitative approach, using quantitative approaches of descriptive statistics and correlation. Firstly, a survey was made according to the number of agroindustrial establishments, by quantity and type, number of individuals and families, sex and educational level, as well as land tenure, motivation to start an activity and areas size of the families. As a result, the institutions and organizations that promote agroindustrialization in Ubiratã were presented, as well as the activities that each one promotes as well as what kind of relationship each entity keeps with each other. Then, the types of tools and management controls were identified and used in each unit of household production, followed by the analysis of aspects such as production, market, health, financial and legal aspects and costs. In addition, it was made a survey of: income sources, agroindustry participation on family income and agroindustrialization significance for each family. Based on this information, keyelements were identified concerning management/administration, which are essential for process and rural development design through agricultural industries family. It was possible to identify that the presence of familiar agro-industries in Ubiratã-PR city has unique features of a successful familiar agriculture, as a successful kind of modern and conventional agriculture. But, at the same time, it keeps peasants’ characteristics in its cultural identity and social interactions. Those several kinds of agro-industry, number of persons employed and quality of life put forward by the familiar agro-industrialization project (an alternative of rural development) have disclosed the need to improve interactions between institutions and support organizations to agro-industrialization in this Municipality. This happens to consolidate some more efficient network management and encourage new initiatives. But, in relation to the management in agro-industrial establishments, better professional features are necessary to use tools and managerial controls on producers’ part, in order to guarantee better adaptation to them with regard to the current market and to increase the perspectives to look for new spaces and, thus guaranteeing sustainability, autonomy and expansion of decision-making capacity on carrying out their enterprises.